Akuntabilitas Pengelolaan Alokasi Dana Desa Tirto Asri di Kecamatan Taluditi Kabupaten Pohuwato Tahun 2015 - Umar Sune; Rusni Djafar (Universitas Islam Darul Ulum Lamongan, 2022)
This study looks at how the Village Fund Allocation financial management is implemented by the village government of Tirto Asri. The Village Fund Allocation management process involves the community from the planning stage to supervision. Even though the Village Fund Allocation management is very good, the community's understanding of the Village Fund Allocation policy is still low. In terms of Village Fund reporting carried out by the Tirto Asri village government through the PSID institution, it is very good. Reporting is carried out using digital information media, information distributed by each hamlet through the RT head and the hamlet head, as well as information boards placed at the Village Office. Implementation of Village Fund Allocation accountability by the village government technically and administratively is good. But in terms of reports on the realization of the use of Village Fund Allocations, the village government only makes reports in a makeshift report format. Because there are no specific rules that discuss the format that should be done. BPD in carrying out its functions is running well but not optimal. This is because there are several factors that create obstacles, namely Human Resources (HR).